Watkins and Graham Families at Bass Lake - Watkins, Howard::::::::: (1989)
Group photo: standing: Adam Watkins, Jesse Graham, Peter Graham, Howard Watkins, Robin Watkins; seated: Christine Watkins, Frances Kamp and Richard Graham; beach and lake in background